The influence of prior accumulated fatigue on power output in professional cyclists - Giorgi, A.; Martinez-Gonzalez, B.; Leo, P. (Journal of Science and Cycling, 2021)
Maximum performance capacity, i.e., power profile of a cyclist, could be assessed in the field through the analysis of mean maximal power output (MMP) over different durations. Only little is known about how prior accumulated fatigue influences MMP. Several studies analysed MMP data in professional cyclists of training and racing (Leo et al 2020; Van Erp et al 2021). These authors highlighted that the decline in MMP after an amount of work could be an important parameter for assessing fatigue resistance in professional cycling. For this reason, our aim is to investigate whether prior continuous or intermittent exercise before an MMP test may influence a decline in performance